The political economy of public pensions - Norcross, Eileen; Smith, Daniel J., 1984- (Cambridge : Cambridge University Press, 2021)
Public pensions in the United States face an impending funding crisis in the wake of the financial crisis and the COVID-19 recession. Many cities and states will struggle to meet these growing obligations without major cuts in government services, reneging on pension promises, or raising taxes. This Element examines the development of the pension crisis through the lens of political economy. We analyze the knowledge and incentive problems inherent in the institutional structure, governance, and accounting of public pensions. We conclude by offering several institutional, governance, and reporting reforms to address the pension funding crisis.
Title from publisher's bibliographic system (viewed on 29 Jul 2021).
Keywords: Social security -- United States